Hydrogeochemical characteristics and genesis of Hongshuilantang Hot Spring and its water temperature anomalies during the Rushan earthquake swarm in Eastern China - Du, Guilin; Su, Shujuan; Chang, Xiangchun; Ren, Hongwei; Huo, Zhuqing; Zhang, Xiaohui (Frontiers in Earth Science, 2023)
Water temperatures of hot springs close to tectonic fault zones often show some variations before earthquakes, and analyses of earthquake precursors in hot springs have significant referential meaning for earthquake monitoring and forecasting. This study measured the concentration of major ions in water from the Hongshuilantang Hot Spring in 2017 and 2020. The ion composition was classified by hydrochemistry into the HCO3·SO4-Na chemical type. The composition of hydrogen and oxygen isotopes in the Hongshuilantang Hot Spring were located near the global meteoric water line (GMWL), indicating that the recharge source of the hot spring was meteoric water. The δD and δ18O values were not plotted on the Glogal Meteroric Water Line (GMWL), and there were some deviations, which suggested that hot spring water underwent water–rock interactions. Deep circulation water played an important role during the evolution process of thermal water. Water temperature showed a decreasing trend from October 2013 to June 2015 during the Rushan earthquake swarm in eastern China. Because of the occurrence of the earthquake swarm, we inferred that regional stress in this area began to be released, allowing continuous rebalancing. Free surface water appeared in some aquifers, and the seepage of low-temperature underground water into the upper aquifer led to a drop in water temperature in the hot spring. The Hongshuilantang Hot Spring and the epicenter of the Rushan earthquake swarm were located on the Muping–Jimo seismological fault zone, with the same seismotectonic system and some genesis relationships.